PENDAMPINGAN ANGGOTA KOPERASI KARTINI JAYA DESA SOKO BANDUNG TULUNGAGUNG DENGAN TEMA STRATEGI MEMPERTAHANKAN UMKM DI ERA PANDEMI COVID-19 - Fatik Lutfiana Anggraini (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2021)
This service aims to minimize the impact of the pandemi on the community's economy. The location of the service is in Soko Village, Bandung, Tulungagung. The method in this activity is the presentation lecture method, this method was chosen to convey important concepts to be understood and mastered by the trainees. The use of this method is based on the consideration that the lecture method combined with pictures, animations and displays can provide relatively large amounts of material in a dense, fast and easy manner. The location of the service is in Soko Village, Bandung, Tulungagung. The target of this activity is the 26 members of the Kartini Jaya Cooperative, Soko Village, Bandung District, Tulungagung Regency. The results of the service show that these activities provide opportunities for cooperative members who have MSMEs. In addition, there has been an increase in maintaining business that has occurred in the Kartini Jaya cooperative, indicated by changes that lead to increasing business competitiveness, including increasing job satisfaction, the emergence of new businesses from members, creativity of members in trading, having a strong will. in working to be more independent and, less afraid of the pandemi.